A photovoltaic backsheet film material and its preparation method

CN122941118APending Publication Date: 2026-10-20苏州锐驰朗新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611355079.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,氟素薄膜成本高昂,加工难度大,且含氟材料在焚烧或长期废弃后存在环境争议,制约了光伏发电全生命周期的绿色属性

Benefits of technology

本发明针对现有光伏背板薄膜在耐热性、尺寸稳定性、长期耐久性与电气绝缘性之间难以兼顾的瓶颈,提供一种综合性能更优的硅烷交联CPVC/PVC纳米复合薄膜。通过CPVC与PVC在特定聚合度与氯含量范围内的调配,配合由高分子量聚酯增塑剂、偏苯三酸三辛酯及含环氧基团反应型增塑剂构成的复合增塑剂体系,以及钙锌复合稳定剂与辅助稳定剂的协同热稳定体系,使薄膜兼具优良柔韧性、加工流动性与突出的耐热抗收缩能力。硅烷接枝交联体系在特定工艺下形成稳定的三维网络结构,不仅赋予薄膜优异的尺寸稳定性和抗蠕变性能,还通过协同机制显著抑制增塑剂迁移与挥发,大幅提升湿热老化过程中的性能保有率;短切玻璃纤维与经表面活化的纳米二氧化硅、纳米碳酸钙、纳米氧化锌等多尺度填料合理复配,在交联网络基础上构建多级增强与裂纹偏转耗能机制,既有效提升拉伸和抗撕裂性能,又通过骨架锚定效应进一步抑制高温收缩与分子链松弛。同时,金红石型钛白粉与纳米氧化锌作为无机紫外屏蔽组分,与有机紫外线吸收剂、受阻胺光稳定剂及抗氧剂构成多重光稳定体系,通过物理屏障、化学吸收与自由基清除的分层协同防护,使薄膜在强紫外辐照后仍保持良好外观与力学性能,避免单纯依赖有机稳定剂时的消耗失效问题。本发明从配方、微观结构到制备工艺协同优化,使薄膜在耐热、抗紫外老化、抗湿热老化、增塑剂抗迁移、电气绝缘、水汽阻隔及与EVA层压粘接可靠性等方面得到提高,能够满足光伏组件在严苛户外环境下对背板材料的长寿命、高可靠与高安全要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention belongs to the field of photovoltaic module encapsulation materials technology, specifically relating to a photovoltaic backsheet film material and its preparation method. The invention uses chlorinated polyvinyl chloride and a polyvinyl chloride alloy as the matrix, combined with a composite plasticizing system consisting of a migration-resistant plasticizer and a reactive epoxy plasticizer, a calcium-zinc composite heat-stabilizing system, and an acrylate impact modifier; it introduces a silane grafting moisture crosslinking system to form a three-dimensional network structure, and simultaneously incorporates short-cut glass fibers and surface-activated nano-silica, nano-calcium carbonate, and nano-zinc oxide fillers, constructing a synergistic light-stabilizing system of inorganic UV shielding agents and organic light stabilizers. The preparation method uses a twin-screw extruder for zoned feeding to complete silane grafting, followed by intensive mixing and plasticizing, five-roll calendering for film formation, and constant temperature and humidity crosslinking to obtain the finished product. The resulting film material exhibits excellent comprehensive performance in terms of heat resistance, dimensional stability, long-term weather resistance, electrical insulation, and water vapor barrier properties, meeting the long-term outdoor service requirements of photovoltaic modules.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photovoltaic module encapsulation materials technology, specifically relating to a photovoltaic backsheet film material and its preparation method. Background Technology

[0002] Photovoltaic power generation, as a clean and renewable energy source, plays an increasingly important role in the global energy structure transformation. Photovoltaic modules typically need to operate stably in outdoor environments for over 25 years. The backsheet material, as a crucial barrier protecting the modules from moisture, ultraviolet radiation, temperature variations, and mechanical damage, has a decisive impact on the long-term reliability and power generation efficiency of the modules. With the continuous advancement of cost reduction and efficiency improvement in the photovoltaic industry, module power density is constantly increasing, and operating temperatures are correspondingly rising. At the same time, installation scenarios are becoming increasingly diversified, expanding from desert power plants to complex environments such as water surfaces, rooftops, and agricultural complexes. This places more stringent requirements on the heat resistance, weather resistance, electrical insulation, and dimensional stability of backsheet materials.

[0003] Currently, the mainstream solution in the photovoltaic backsheet market is a composite structure containing fluorinated films (such as PVF and PVDF), which dominates the market due to its excellent weather resistance and barrier properties. However, fluorinated films are expensive, difficult to process, and raise environmental concerns regarding the incineration or long-term disposal of fluorinated materials, thus hindering the green attributes of photovoltaic power generation throughout its entire lifecycle. Another approach uses polyethylene terephthalate (PET) as the substrate, improving weather resistance through surface coatings or composite modifications. However, the inherent hydrolytic sensitivity of PET materials causes significant performance degradation in humid and hot environments, making it difficult to meet the long-term use requirements of coastal or high-humidity areas. While polyolefin backsheet materials are lower in cost, their heat resistance and creep resistance are insufficient, making them prone to shrinkage or deformation during high-temperature lamination processes and outdoor temperature cycling, leading to reliability issues such as microcracks in the cells or circuit connection failures.

[0004] Chlorinated polyvinyl chloride (CPVC) and polyvinyl chloride (PVC), as widely available and cost-effective general-purpose plastics, have natural advantages in chemical corrosion resistance, flame retardancy, and electrical insulation. However, both are thermoplastics, and their heat resistance and dimensional stability are significantly affected by temperature, falling far short of the requirements for photovoltaic backsheets in lamination processes (around 150℃) and long-term outdoor thermal and oxidative aging scenarios. To address this, the industry has attempted to improve processing performance and flexibility by adding large amounts of plasticizers, but this has led to a series of problems such as plasticizer migration and precipitation, surface adhesion, and decreased peel strength from the EVA encapsulation film. While adding rigid fillers can improve modulus and heat resistance, it often results in increased film brittleness, processing difficulties, and filler agglomeration, severely affecting film uniformity and electrical reliability. Although peroxide or radiation crosslinking can improve the heat resistance of the polymer, for CPVC / PVC systems, excessively high crosslinking temperatures can easily trigger resin dehydrochlorination degradation. Radiation crosslinking, on the other hand, faces limitations such as high equipment investment, low production efficiency, and uneven crosslinking in thick products, making it difficult to achieve continuous industrial production. Silane grafting crosslinking technology has been applied in systems such as polyethylene and polyvinyl chloride. However, conventional silane grafting processes require the introduction of water vapor during mixing or extrusion to promote crosslinking. This makes the process extremely sensitive to the control of the processing temperature window and residence time. For blended systems such as CPVC / PVC with relatively weak thermal stability, it is necessary to ensure the effective progress of the silane grafting reaction, avoid the thermal degradation of the resin, and simultaneously ensure the uniform dispersion of the multi-component filler system. These contradictions restrict each other, and existing technologies lack effective process solutions.

[0005] Furthermore, existing technologies for UV protection largely rely on organic UV absorbers and hindered amine light stabilizers. However, for photovoltaic backsheets with an outdoor service life exceeding 25 years, these organic stabilizers gradually deplete under strong UV radiation and alternating hot and humid conditions, leading to an accelerated decline in protective effectiveness over time. Simultaneously, existing backsheet materials often exhibit a significant increase in water vapor permeability and a decrease in volume resistivity after high-temperature and high-humidity aging, exacerbating the risk of internal circuit corrosion and reducing insulation safety margin. In conclusion, developing a thin-film material for photovoltaic backsheets that combines excellent heat resistance, dimensional stability, long-term weather resistance, high electrical insulation, and good economic efficiency, while simultaneously establishing a continuous and large-scale production process, remains a pressing technical challenge in this field. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a photovoltaic backsheet film material and its preparation method.

[0007] The purpose of this invention is to provide a novel backsheet film material that offers superior heat resistance, dimensional stability, long-term weather resistance, electrical insulation, and economic efficiency, and enables continuous and stable production.

[0008] The first aspect of this invention provides a photovoltaic backsheet film material, comprising the following components by weight: Base resin: 50-80 parts of chlorinated polyvinyl chloride, 20-50 parts of polyvinyl chloride; Plasticizer system: 20-35 parts; Heat stabilizer system: 4-6 parts; Impact modifier: 6-10 parts; Fillers and reinforcing materials: 4-6 parts of rutile titanium dioxide, 6-10 parts of nano calcium carbonate, 6-10 parts of chopped glass fiber, 1-3 parts of nano silica, and 1-2 parts of nano zinc oxide; Light-stabilized system: 0.6~1.2 parts; Crosslinking system: 1.5~2.5 parts silane coupling agent, 0.06~0.12 parts peroxide initiator, and 0.06~0.10 parts condensation catalyst.

[0009] Furthermore, the mass ratio of chlorinated polyvinyl chloride to polyvinyl chloride is (60~70):(30~40); The chlorine content of chlorinated polyvinyl chloride is 63%~69%, and the degree of polymerization is 900~1100; the polyvinyl chloride is a suspension loose resin of type SG-3 to SG-5, with a degree of polymerization of 1000~1500. The plasticizer system includes polyester-type plasticizers with a molecular weight of not less than 2000 and reactive plasticizers with epoxy groups; In the filler and reinforcing materials, the nano-silica is fumed silica that has been surface-grafted and activated by a vinyl silane coupling agent, and the chopped glass fibers are surface-treated with a silane coupling agent.

[0010] Furthermore, the plasticizer system is selected from one or more of the following: trioctyl trimellitate, dioctyl terephthalate, adipic acid polyester plasticizer, epoxidized soybean oil, and epoxidized fatty acid methyl ester; wherein, the amount of polyester plasticizer with a molecular weight of not less than 2000 is 4 to 8 parts by mass, the total amount of reactive plasticizer with epoxy groups is 5 to 9 parts by mass, and the reactive plasticizer with epoxy groups is epoxidized soybean oil and / or epoxidized fatty acid methyl ester.

[0011] Furthermore, the heat stabilizer system is selected from one or more of calcium-zinc composite stabilizers, β-diketone stabilizers, phosphite auxiliary stabilizers, and magnesium-aluminum hydrotalcite; the impact modifier is selected from one or two of acrylate core-shell structure impact modifiers, chlorinated polyethylene, and methyl methacrylate-butadiene-styrene copolymer.

[0012] Furthermore, the average particle size of rutile titanium dioxide is 0.2~0.3μm; the average particle size of nano-calcium carbonate is 40~80nm; the fiber diameter of chopped glass fiber is 10~15μm and the length is 2~4mm; the nano-silica is fumed silica with a specific surface area of ​​150~250m² / g and a primary particle size of 10~25nm; and the average particle size of nano-zinc oxide is 30~50nm.

[0013] Furthermore, the light-stabilizing system is selected from one or more of benzotriazole ultraviolet absorbers, hindered amine light stabilizers, and hindered phenolic main antioxidants; the silane coupling agent is vinyltrimethoxysilane or vinyltriethoxysilane; the peroxide initiator is dicumyl peroxide or benzoyl peroxide; and the condensation catalyst is dibutyltin dilaurate or dibutyltin diacetate.

[0014] A second aspect of the present invention provides a method for preparing the above-mentioned photovoltaic backsheet film material, comprising the following steps: Chlorinated polyvinyl chloride resin and polyvinyl chloride resin are dried until the moisture content drops below 0.3%; nano-silica is pre-treated with a vinyl silane coupling agent for surface grafting activation; nano-calcium carbonate is dried; The dried chlorinated polyvinyl chloride, polyvinyl chloride, heat stabilizer, impact modifier, rutile titanium dioxide, nano calcium carbonate, activated nano silica, nano zinc oxide, and light stabilizer are premixed and added to the main feed port of a co-rotating twin-screw extruder; liquid plasticizer is metered and injected from the middle section of the extruder; chopped glass fiber is added from the side feed port of the rear section of the extruder; silane coupling agent and peroxide initiator dissolved therein are injected from a dedicated metering pump in the rear section of the extruder; extrusion granulation is performed to obtain silane grafted alloy granules; The condensation catalyst is melt-mixed with polyethylene wax, cooled and solidified, then pulverized and sieved to prepare catalyst master powder; silane grafted alloy granules are mixed with catalyst master powder, and discharged after cold mixing. After cold mixing, the material is plasticized by internal mixing or open milling and then sheeted out, and then calendered into film by calendering. After calendering, the film is cooled, trimmed, and wound up. The wound film is placed under constant temperature and humidity conditions for post-crosslinking treatment, and then cooled and dried to obtain the finished film.

[0015] Furthermore, the temperatures of each section of the co-rotating twin-screw extruder in the steps are as follows: Zone 1 130~140℃, Zone 2 145~155℃, Zone 3 155~165℃, Zone 4 160~170℃, Zone 5 165~175℃, Zone 6 170~175℃, Zone 7 168~172℃, Zone 8 165~170℃, Zone 9 162~168℃, and Die head 168~172℃; the screw speed is 80~120rpm, and the material residence time in the barrel is 90~150 seconds; the liquid plasticizer is metered and injected from Zone 3, the chopped glass fiber is added from the side feed port of Zone 5, and the silane coupling agent and peroxide initiator are injected from a dedicated metering pump in Zone 6; Zone 8 is equipped with vacuum exhaust, and the vacuum degree is -0.08~-0.095MPa.

[0016] Furthermore, the calender used in this step is a five-roll calender, with the following roll temperatures: Roll 1: 165~170℃, Roll 2: 170~175℃, Roll 3: 175~180℃, Roll 4: 172~177℃, Roll 5: 168~173℃; the final roll gap is 1.08~1.12 times the target film thickness; and the calendering line speed is 8~12m / min.

[0017] Furthermore, the film roll undergoes step cooling via 5 to 7 cooling rollers, with the temperature of the cooling rollers decreasing sequentially from 105 to 115°C to 20 to 30°C; the winding tension is 3 to 5 N / cm, and the film roll remains loosely wound.

[0018] Furthermore, the post-crosslinking treatment conditions in the steps are: temperature 75~85℃, relative humidity 90%~98%, treatment time 20~28 hours; cooling rate not exceeding 1.5℃ / min.

[0019] Further, in the step, the melting point of polyethylene wax is 100~110℃. The condensation catalyst and polyethylene wax are melted and mixed at 60~70℃ and pulverized through a 100-mesh sieve to obtain catalyst master powder. The silane grafted alloy granules and catalyst master powder are stirred at low speed in a high-speed mixer and heated to 75~85℃. After adding the catalyst master powder, the mixture is stirred at high speed to 100~105℃ and maintained for 2~5 minutes. Then, it is cooled to 35~40℃ by a cold mixer before being discharged.

[0020] Beneficial effects This invention addresses the bottleneck of existing photovoltaic backsheet films in achieving a balance between heat resistance, dimensional stability, long-term durability, and electrical insulation, providing a silane-crosslinked CPVC / PVC nanocomposite film with superior overall performance. By adjusting the polymerization degree and chlorine content of CPVC and PVC within a specific range, and combining them with a composite plasticizer system consisting of a high-molecular-weight polyester plasticizer, trioctyl trimellitate, and a reactive plasticizer containing epoxy groups, as well as a synergistic heat-stabilizing system of calcium-zinc composite stabilizers and auxiliary stabilizers, the film possesses excellent flexibility, processing fluidity, and outstanding heat resistance and shrinkage resistance. The silane grafted crosslinking system forms a stable three-dimensional network structure under specific processes, which not only endows the film with excellent dimensional stability and creep resistance, but also significantly inhibits plasticizer migration and volatilization through a synergistic mechanism, greatly improving the performance retention rate during hygrothermal aging. Short-cut glass fibers are rationally compounded with multi-scale fillers such as surface-activated nano-silica, nano-calcium carbonate, and nano-zinc oxide to construct a multi-level reinforcement and crack deflection energy dissipation mechanism on the basis of the crosslinked network. This effectively improves tensile and tear resistance, and further inhibits high-temperature shrinkage and molecular chain relaxation through the skeleton anchoring effect. Meanwhile, rutile titanium dioxide and nano-zinc oxide, as inorganic UV shielding components, together with organic UV absorbers, hindered amine light stabilizers, and antioxidants, form a multi-layered light-stabilizing system. Through layered synergistic protection of physical barriers, chemical absorption, and free radical scavenging, the film maintains good appearance and mechanical properties after strong UV irradiation, avoiding the consumption failure problem that occurs when relying solely on organic stabilizers. This invention achieves synergistic optimization from formulation and microstructure to preparation process, thereby improving the film's heat resistance, UV aging resistance, damp heat aging resistance, plasticizer migration resistance, electrical insulation, moisture barrier properties, and reliability of EVA lamination bonding. This enables it to meet the long lifespan, high reliability, and high safety requirements of photovoltaic modules for backsheet materials in harsh outdoor environments. Detailed Implementation

[0021] The silane crosslinked CPVC / PVC nanocomposite film for photovoltaic backsheets provided by this invention comprises, by weight, a base resin consisting of chlorinated polyvinyl chloride (CPVC) and polyvinyl chloride (PVC), wherein the chlorine content of CPVC is 63%~69% and the degree of polymerization is 900~1100; the PVC is an SG-3 to SG-5 type suspension loose resin with a degree of polymerization of 1000~1500. The mass ratio of CPVC to PVC can be (50~80):(20~50), preferably (60~70):(30~40).

[0022] The plasticizer system can be selected from one or more of the following: trioctyl trimellitate (TOTM), dioctyl terephthalate (DOTP), adipic acid polyester plasticizer, epoxidized soybean oil (ESO), and epoxidized fatty acid methyl ester (EFAME), with a total dosage of 20-35 parts by mass. Among them, the dosage of polyester-type plasticizers with a molecular weight of not less than 2000 can be 4-8 parts by mass, and the total dosage of reactive plasticizers with epoxy groups (ESO, EFAME) can be 5-9 parts by mass.

[0023] The heat stabilizer system can be selected from one or more of calcium-zinc composite stabilizers, β-diketone stabilizers, phosphite auxiliary stabilizers, and magnesium-aluminum hydrotalcite, with a total dosage of 4 to 6 parts by weight. The impact modifier can be selected from one or two of acrylate core-shell structure impact modifiers (ACR), chlorinated polyethylene (CPE), and methyl methacrylate-butadiene-styrene copolymer (MBS), with a total dosage of 6 to 10 parts by weight.

[0024] The fillers and reinforcing materials include one or more of rutile titanium dioxide, nano-calcium carbonate, chopped glass fiber, nano-silica, and nano-zinc oxide. The amount of rutile titanium dioxide can be 4-6 parts by weight, with an average particle size of 0.2-0.3 μm; the amount of nano-calcium carbonate can be 6-10 parts by weight, with an average particle size of 40-80 nm; the amount of chopped glass fiber can be 6-10 parts by weight, with a fiber diameter of 10-15 μm and a length of 2-4 mm, and surface-treated with a silane coupling agent; the amount of nano-silica can be 1-3 parts by weight, which is fumed silica with a specific surface area of ​​150-250 m² / g and a native particle size of 10-25 nm, preferably surface-grafted and activated with vinyltrimethoxysilane; the amount of nano-zinc oxide can be 1-2 parts by weight, with an average particle size of 30-50 nm.

[0025] The light-stabilizing system can be selected from one or more of benzotriazole ultraviolet absorbers, hindered amine light stabilizers (HALS), and hindered phenolic main antioxidants, and the total amount can be 0.6 to 1.2 parts by weight.

[0026] The crosslinking system consists of a silane coupling agent, a peroxide initiator, and an organotin catalyst. The silane coupling agent can be selected from vinyltrimethoxysilane (VTMO) or vinyltriethoxysilane (VTEO), and the amount used can be 1.5 to 2.5 parts by mass; the peroxide initiator can be selected from dicumyl peroxide (DCP) or benzoyl peroxide (BPO), and the amount used can be 0.06 to 0.12 parts by mass; the condensation catalyst can be selected from dibutyltin dilaurate (DBTDL) or dibutyltin diacetate, and the amount used can be 0.06 to 0.10 parts by mass.

[0027] The preparation method of the film of the present invention includes the following steps: (1) CPVC resin and PVC resin are dried at 70~90℃ for 3~5 hours to reduce the moisture content to below 0.3%; nano silica is pre-treated with vinyl silane coupling agent for surface grafting activation; nano calcium carbonate is dried at 100~110℃ for 1~3 hours. (2) The dried CPVC, PVC and heat stabilizer, impact modifier, processing aid, lubricant, titanium dioxide, nano calcium carbonate, activated nano silica, nano zinc oxide and light stabilizer are pre-mixed in proportion and added to the main feed port of the co-rotating twin-screw extruder; liquid plasticizer and phosphite are metered and injected from zone 3; chopped glass fiber is added from the side feed port of zone 5; silane coupling agent and peroxide initiator dissolved therein are injected from the special metering pump in zone 6; the temperature of each section of the twin-screw extruder is 130~140℃ in zone 1 and 145~155℃ in zone 2. Zones 3, 155-165℃; Zone 4, 160-170℃; Zone 5, 165-175℃; Zone 6, 170-175℃; Zone 7, 168-172℃; Zone 8, 165-170℃; Zone 9, 162-168℃; Die head, 168-172℃; Screw speed, 80-120 rpm; Material residence time in barrel, 90-150 seconds; Zone 8, vacuum exhaust, vacuum degree, -0.08--0.095 MPa; Extrudate is pelletized by water ring cutting or cold drawing, dried at 80℃ for 2 hours to obtain silane-grafted CPVC / PVC alloy granules. (3) The organotin catalyst is melted and mixed with polyethylene wax with a melting point of 100~110℃ at 60~70℃, cooled and solidified, and then crushed through a 100-mesh sieve to make catalyst master powder; silane grafted granules are added to a high-speed mixer, and heated to 75~85℃ by friction under low-speed stirring, catalyst master powder is added, and high-speed stirring is continued to 100~105℃ and maintained for 2~5 minutes, and then discharged into a cold mixer to cool to 35~40℃ before discharge. (4) The cold-mixed material is internally mixed at 160~170℃ for 3~5 minutes, or directly plasticized on a two-roll mill at 170~178℃ for 5~8 minutes, and then sheeted at 168~172℃; the sheet is fed into a five-roll calender to calender into film. The temperature of each roll of the calender is 165~170℃ for roll #1, 170~175℃ for roll #2, 175~180℃ for roll #3, 172~177℃ for roll #4, and 168~173℃ for roll #5; the final roll gap is set to 1.08~1.12 times the target film thickness according to the target film thickness; the calendering line speed is 8~12m / min. (5) After calendering, the film is cooled by 5 to 7 cooling rollers in a step-by-step manner, with the temperature of the cooling rollers decreasing from 105 to 115°C to 20 to 30°C in sequence; after trimming, the film is wound up under a tension of 3 to 5 N / cm, and the film roll is kept in a loose state.(6) Place the wound film in a constant temperature and humidity chamber and treat it at 75~85℃ and 90%~98% relative humidity for 20~28 hours to allow the silane to complete hydrolysis, condensation and crosslinking; then cool it to room temperature at a rate not exceeding 1.5℃ / min, dry it at 40℃ for 2 hours and then rewind and package it.

[0028] The present invention is further illustrated below with specific embodiments. These embodiments are exemplary and intended to illustrate the problem and explain the present invention, and are not intended to be limiting.

[0029] Example 1 This embodiment provides a silane-crosslinked CPVC / PVC nanocomposite film for photovoltaic backsheets, which, by weight, comprises the following components: 65 parts CPVC resin (chlorine content 66%, degree of polymerization 1000), 35 parts PVC resin (SG-3 type, degree of polymerization 1300), 15 parts trioctyl trimellitate (TOTM), 6 parts adipic acid polyester plasticizer (molecular weight 2000~3000), 4 parts epoxidized soybean oil (ESO), 3 parts epoxidized fatty acid methyl ester (EFAME), 3.5 parts calcium-zinc composite stabilizer, 0.5 parts dibenzoylmethane, 0.5 parts trinonylphenyl phosphite, 0.5 parts magnesium aluminum hydrotalcite, and ACR core-shell... Impact modifier 5 parts, chlorinated polyethylene (chlorine content 35%) 3 parts, ACR processing aid 1.2 parts, calcium stearate 0.6 parts, polyethylene wax 0.3 parts, oxidized polyethylene wax 0.2 parts, stearic acid 0.2 parts, rutile titanium dioxide 5 parts, nano calcium carbonate (average particle size 60nm, stearic acid treated) 8 parts, chopped glass fiber (diameter 13μm, length 3mm, silane treated) 8 parts, nano silica (gas phase method, specific surface area 200m² / g, surface-grafted and activated by VTMO) 2 parts, nano zinc oxide (average particle size 40nm) 1.5 parts, UV-326 ultraviolet absorber 0.4 parts, Chimassorb 0.3 parts of hindered amine light stabilizer 944, 0.2 parts of antioxidant 1010, 2.0 parts of vinyltrimethoxysilane (VTMO), 0.08 parts of dicumyl peroxide (DCP), and 0.08 parts of dibutyltin dilaurate (DBTDL).

[0030] The preparation method is as follows: CPVC and PVC resin were dried in an 80℃ forced-air oven for 4 hours, turning them over every hour until the moisture content was 0.22%. Nano-calcium carbonate was dried at 105℃ for 2 hours. 20g of fumed silica was dispersed in 500mL of ethanol and ultrasonically dispersed for 30 minutes. Separately, 100g of ethanol / water (95:5) solution was taken, the pH was adjusted to 4.5~5.0 with acetic acid, 0.4g of VTMO was added, and the solution was stirred and hydrolyzed at 25℃ for 30 minutes. The hydrolysate was slowly added dropwise to the silica suspension, reacted at 60℃ for 3 hours, centrifuged, washed twice with ethanol, vacuum dried at 80℃ for 4 hours, and ground through a 200-mesh sieve to obtain silane-grafted activated nano-silica.

[0031] The dried CPVC, PVC, calcium-zinc stabilizer, dibenzoylmethane, hydrotalcite, ACR impact modifier, CPE, ACR processing aid, calcium stearate, polyethylene wax, oxidized polyethylene wax, stearic acid, titanium dioxide, nano calcium carbonate, activated nano silica, nano zinc oxide, UV-326, Chimassorb 944, and antioxidant 1010 are premixed for 5 minutes in a high-speed mixer and added to the main feed port of a co-rotating twin-screw extruder (screw diameter 35mm, L / D ratio 44:1). TOTM, polyester plasticizer, ESO, EFAME, and TNPP are mixed and injected from the metering pump in zone 3. Chopped glass fibers are added from the loss-in-weight side feed in zone 5. 0.08 parts of DCP are dissolved in 2.0 parts of VTMO and injected from the dedicated metering pump in zone 6. The temperature settings for each section of the twin-screw extruder are as follows: Zone 1 135℃, Zone 2 150℃, Zone 3 160℃, Zone 4 165℃, Zone 5 170℃, Zone 6 172℃, Zone 7 170℃, Zone 8 168℃, Zone 9 165℃, and Die 170℃; Screw speed 100 rpm, feed rate 10 kg / h, and vacuum degree of Zone 8 -0.09 MPa; The extrudate is granulated by a water ring, and the particles are dried at 80℃ for 2 hours with a moisture content of 0.15% to obtain silane-grafted CPVC / PVC alloy granules.

[0032] 0.08 parts of DBTDL and 0.8 parts of polyethylene wax were melted and mixed evenly at 65°C. After cooling and solidification, the mixture was pulverized through a 100-mesh sieve to obtain catalyst masterbatch. 1000g of grafted granules were added to a high-speed mixer and stirred at 400rpm to raise the temperature to 80°C. The catalyst masterbatch was added, and the mixture was stirred at 1200rpm to raise the temperature to 102°C and maintained for 3 minutes. The mixture was then discharged to a cold mixer and stirred at 250rpm to cool it to 38°C before being discharged.

[0033] The cold-mixed material was added to a 1L internal mixer, the temperature was set to 165℃, the top bolt pressure to 0.5MPa, and the mixing was carried out for 3.5 minutes. The discharge temperature was 166℃, and the material clump was in a uniform plasticized state. The mixed material was then passed through a two-roll mill for 6 minutes at a front roll temperature of 175℃, a rear roll temperature of 172℃, and a roll gap of 0.12mm. The mill was then folded 9 times with a cutter. The roll gap was then increased to 0.7mm, the front roll temperature was set to 170℃, and the rear roll temperature was set to 168℃. The mill was then sheeted for 1.5 minutes to obtain a sheet with a thickness of approximately 0.7mm.

[0034] The sheet material is fed into a five-roll calender. Roll #1 is heated to 168°C, roll #2 to 172°C, roll #3 to 178°C, roll #4 to 175°C, and roll #5 to 170°C. The roll gaps are 0.80mm, 0.45mm, 0.33mm, and 0.28mm, respectively. The linear speed of roll #3 is 10m / min, and the speed ratio of each roll is 1:1.05:1.08:1.05:1.02. The calendered film is then cooled in stages by seven cooling rolls at temperatures of 110°C, 90°C, 70°C, 50°C, 35°C, 25°C, and 25°C, respectively. 18mm of waste edge is removed from both sides, and the film is wound up under a tension of 4N / cm, resulting in a film thickness of 0.255mm.

[0035] The film roll was loosely placed in a constant temperature and humidity chamber, heated to 80°C at 2°C / min, and treated at 95% relative humidity for 24 hours; then cooled to room temperature at 1°C / min, dried at 40°C for 2 hours, and rewound to obtain the finished film.

[0036] Example 2 This embodiment provides a silane-crosslinked CPVC / PVC nanocomposite film for photovoltaic backsheets, which, by weight, comprises the following components: 55 parts CPVC resin (chlorine content 65%, degree of polymerization 950), 45 parts PVC resin (SG-3 type, degree of polymerization 1350), 13 parts TOTM, 5 parts adipic acid polyester plasticizer, 3 parts ESO, 3 parts EFAME, 3.2 parts calcium-zinc composite stabilizer, 0.4 parts dibenzoylmethane, 0.5 parts TNPP, 0.4 parts magnesium aluminum hydrotalcite, 5 parts ACR impact modifier, 3 parts CPE, 1.2 parts ACR processing aid, 0.6 parts calcium stearate, 0.3 parts polyethylene wax, 0.2 parts oxidized polyethylene wax, 0.2 parts stearic acid, 5 parts rutile titanium dioxide, 8 parts nano calcium carbonate, 7 parts chopped glass fiber, 1.5 parts silane-activated nano silica, 1.5 parts nano zinc oxide, and UV-326. 0.4 parts, Chimassorb 944 0.3 parts, Antioxidant 1010 0.2 parts, VTMO 1.8 parts, DCP 0.07 parts, DBTDL 0.07 parts.

[0037] The preparation method is basically the same as in Example 1, except that: the overall twin-screw extrusion temperature is reduced by 2°C, the screw speed is 110 rpm; the mixing temperature is 163°C, the mixing time is 4 minutes; the calender roll temperature is 176°C; and the post-crosslinking conditions are 78°C, 95%RH, and 24 hours.

[0038] Example 3 This embodiment provides a silane-crosslinked CPVC / PVC nanocomposite film for photovoltaic backsheets, which, by weight, comprises the following components: 75 parts CPVC resin (chlorine content 68%, degree of polymerization 1050), 25 parts PVC resin (SG-4 type, degree of polymerization 1250), 17 parts TOTM, 7 parts adipic acid polyester plasticizer, 5 parts ESO, 3 parts EFAME, 3.8 parts calcium-zinc composite stabilizer, 0.6 parts dibenzoylmethane, 0.6 parts TNPP, 0.6 parts magnesium aluminum hydrotalcite, 5 parts ACR impact modifier, 3 parts CPE, 1.5 parts ACR processing aid, 0.7 parts calcium stearate, 0.4 parts polyethylene wax, 0.3 parts oxidized polyethylene wax, 0.2 parts stearic acid, 5 parts rutile titanium dioxide, 8 parts nano calcium carbonate, 9 parts chopped glass fiber, 2.5 parts silane-activated nano silica, 1.5 parts nano zinc oxide, and UV-326. 0.4 parts, Chimassorb 944 0.3 parts, Antioxidant 1010 0.2 parts, VTMO 2.3 parts, DCP 0.10 parts, DBTDL 0.09 parts.

[0039] The preparation method is basically the same as in Example 1, except that: the overall twin-screw extrusion temperature is increased by 2°C, the screw speed is 90 rpm, and the residence time is about 130 seconds; the mixing temperature is 168°C and the mixing time is 3 minutes; the open milling time is extended to 7 minutes; the calendering roller temperature is 179°C; and the post-crosslinking conditions are 82°C, 95%RH, and 26 hours.

[0040] Example 4 This embodiment provides a silane-crosslinked CPVC / PVC nanocomposite film for photovoltaic backsheets, which, by weight, comprises the following components: 65 parts CPVC resin, 35 parts PVC resin, 12 parts TOTM, 5 parts adipic acid polyester plasticizer, 3 parts ESO, 2 parts EFAME, 3.5 parts calcium-zinc composite stabilizer, 0.5 parts dibenzoylmethane, 0.5 parts TNPP, 0.5 parts magnesium aluminum hydrotalcite, 6 parts ACR impact modifier, 3 parts CPE, 1.2 parts ACR processing aid, 0.5 parts calcium stearate, 0.3 parts polyethylene wax, 0.2 parts oxidized polyethylene wax, 0.2 parts stearic acid, 5 parts rutile titanium dioxide, 9 parts nano calcium carbonate, 9 parts chopped glass fiber, 2 parts silane-activated nano silica, 1.5 parts nano zinc oxide, 0.4 parts UV-326, 0.3 parts Chimassorb 944, and antioxidant 1010. 0.2 parts, VTMO 2.0 parts, DCP 0.08 parts, DBTDL 0.08 parts. The total amount of plasticizer is 22 parts.

[0041] The preparation method is basically the same as in Example 1, except that the temperature of each calendering roll is increased by 1~2℃ to compensate for the increase in melt viscosity caused by the lower plasticizer content; the post-crosslinking conditions are 80℃, 95%RH, and 24 hours.

[0042] Example 5 This embodiment provides a silane-crosslinked CPVC / PVC nanocomposite film for photovoltaic backsheets, which, by weight, comprises the following components: 65 parts CPVC resin, 35 parts PVC resin, 18 parts TOTM, 7 parts adipic acid polyester plasticizer, 5 parts ESO, 4 parts EFAME, 3.5 parts calcium-zinc composite stabilizer, 0.5 parts dibenzoylmethane, 0.5 parts TNPP, 0.5 parts magnesium aluminum hydrotalcite, 4 parts ACR impact modifier, 3 parts CPE, 1.2 parts ACR processing aid, 0.7 parts calcium stearate, 0.4 parts polyethylene wax, 0.2 parts oxidized polyethylene wax, 0.3 parts stearic acid, 5 parts rutile titanium dioxide, 7 parts nano calcium carbonate, 7 parts chopped glass fiber, 2 parts silane-activated nano silica, 1.5 parts nano zinc oxide, 0.4 parts UV-326, 0.3 parts Chimassorb 944, and antioxidant 1010. 0.2 parts, VTMO 2.0 parts, DCP 0.08 parts, DBTDL 0.08 parts. The total amount of plasticizer is 34 parts.

[0043] The preparation method is basically the same as that in Example 1, except that the temperature of each calendering roller is reduced by 1~2℃; and the post-crosslinking conditions are 80℃, 95%RH, and 24 hours.

[0044] Comparative Example 1 This comparative example provides a conventional flexible PVC film, which, by weight, is composed of the following components: 100 parts of PVC resin (SG-3 type, degree of polymerization 1300), 50 parts of dioctyl phthalate (DOP), 2.0 parts of calcium-zinc composite stabilizer, 0.3 parts of stearic acid, 0.2 parts of polyethylene wax, and 2 parts of rutile titanium dioxide.

[0045] The preparation method is as follows: PVC resin is mixed with stabilizer, lubricant and titanium dioxide at 80°C, DOP is added and stirring is continued at 110°C, and then cold mixed at 40°C; the mixture is plasticized at 165°C for 5 minutes using a two-roll mill and then sheeted out using a four-roll calender to form a 0.25mm film; no silane grafting or post-crosslinking treatment is performed.

[0046] Comparative Example 2 This comparative example provides a CPVC / PVC alloy film with a formulation that is basically the same as that of Example 1. The difference is that VTMO, DCP and DBTDL crosslinking system components are not added; the silane injection step in the sixth zone of the twin-screw extruder is skipped in the preparation process; and the film is not subjected to wet heat crosslinking treatment after calendering and winding. The remaining components and process parameters are the same as those of Example 1.

[0047] Comparative Example 3 This comparative example provides a silane crosslinked CPVC / PVC nanocomposite film with a formulation that is basically the same as that of Example 1, except that: no chopped glass fibers are added; glass fibers are not side-fed in the fifth zone of the twin-screw extruder during the preparation process; and the remaining components and process parameters are the same as those of Example 1.

[0048] Comparative Example 4 This comparative example provides a silane crosslinked CPVC / PVC nanocomposite film with a formulation that is basically the same as that of Example 1, except that 15 parts of TOTM, 6 parts of polyester plasticizer, 4 parts of ESO, and 3 parts of EFAME are replaced with an equal mass (28 parts) of DOP; the remaining components and process parameters are the same as those of Example 1, including silane grafting and post-crosslinking treatment.

[0049] Comparative Example 5 This comparative example provides a silane crosslinked CPVC / PVC nanocomposite film with a formulation that is basically the same as that in Example 1, except that: the nano silica is not subjected to silane grafting activation treatment, and two parts of untreated hydrophilic fumed nano silica (specific surface area 200 m² / g) are used directly; the remaining components and process parameters are the same as those in Example 1.

[0050] Comparative Example 6 This comparative example provides a silane crosslinked CPVC / PVC nanocomposite film with a formulation that is basically the same as that of Example 1, except that: rutile titanium dioxide and nano zinc oxide are not added; the amount of UV-326 is adjusted to 0.8 parts and the amount of Chimassorb944 is adjusted to 0.6 parts; the remaining components and process parameters are the same as those of Example 1.

[0051] Performance testing methods The following performance tests were performed on the films prepared in Examples 1-5 and Comparative Examples 1-6: (1) Gel content determination: Take about 0.5g of film sample, cut it into pieces, wrap it with a 200-mesh copper mesh, place it in a Soxhlet extractor, use tetrahydrofuran as solvent, boil and reflux for 8 hours; take out the insoluble matter, vacuum dry it at 80℃ to constant weight, and calculate the percentage of insoluble matter to the original mass of the sample, which is the gel content.

[0052] (2) Vicat softening temperature: According to GB / T 1633-2000 standard, the A50 method is adopted, that is, 10N load and 50℃ / h heating rate, and the Vicat softening point is tested on the Vicat softening point tester.

[0053] (3) Heat shrinkage rate: According to GB / T 12027-2004 standard, 100mm×100mm samples were cut along the longitudinal (MD) and transverse (TD) directions of the film, and placed freely in a 150℃ hot air circulating oven for 30 minutes. After being taken out and cooled to room temperature, the dimensional changes were measured and the shrinkage rate was calculated.

[0054] (4) Tensile properties: In accordance with GB / T 1040.3-2006 standard, dumbbell-shaped specimens with a gauge length of 50 mm and a tensile speed of 100 mm / min were used to test the tensile strength and elongation at break on a universal testing machine.

[0055] (5) Right-angle tear strength: According to the QB / T 1130-1991 standard, a right-angled specimen is used and tested on a universal testing machine.

[0056] (6) Plasticizer migration weight loss: Cut a 50mm×50mm sample from the film, weigh it, and then place it in a sealed container containing activated carbon. Place it in an oven at 85℃ for 28 days. After taking it out, remove the surface activated carbon with a brush, weigh it, and calculate the mass loss rate.

[0057] (7) Damp heat aging performance: According to IEC 61215 standard, the sample was placed in a constant temperature and humidity chamber at 85℃ and 85% relative humidity for 1000 hours, 2000 hours and 3000 hours respectively. After being taken out, the sample was adjusted to a standard environment for 24 hours, and the tensile strength and elongation at break were tested to calculate the performance retention rate. At the same time, the yellowing index ΔYI was tested with a colorimeter.

[0058] (8) UV aging performance: According to IEC 61215 MQT 19, the aging test was carried out in a xenon lamp aging chamber with a total irradiation of 60 kWh / m², a black standard temperature of 65±3℃, and a cycle condition of 102 minutes of dry irradiation / 18 minutes of spray irradiation. After aging, the tensile strength retention rate and yellowing index were tested.

[0059] (9) Volume resistivity: Tested on a high resistance meter according to GB / T 1410-2006 standard, with a test voltage of 500V; the volume resistivity was tested in the initial state and after aging at 85℃ / 85%RH for 1000 hours.

[0060] (10) Dielectric strength: Tested in insulating oil using the uniform voltage increase method according to GB / T 1408.1-2016 standard.

[0061] (11) Water vapor transmission rate: Tested by an electrolytic water vapor transmission rate tester at 38℃ and 90%RH according to GB / T 26253-2010 standard.

[0062] (12) Peel strength with EVA: The film is laminated with a 0.45mm thick EVA film and a 3.2mm photovoltaic patterned glass, and laminated in a vacuum laminator at 145℃ (vacuum for 5 minutes and pressure for 10 minutes); after cooling, a 15mm wide sample is cut and the 180° peel strength test is performed according to GB / T2790-1995, with a peel speed of 100mm / min.

[0063] (13) Flame retardant performance: The limiting oxygen index is tested according to GB / T 2406.2-2009; the vertical flammability rating is tested according to UL 94 standard.

[0064] Test Results The basic physical and mechanical performance test results of each embodiment and comparative example are shown in Table 1.

[0065] Table 1 Basic Physical and Mechanical Properties The thermal performance and dimensional stability test results of each embodiment and comparative example are shown in Table 2.

[0066] Table 2 Thermal properties and dimensional stability The durability test results of each embodiment and comparative example are shown in Table 3.

[0067] Table 3 Durability Performance The electrical and barrier performance test results of each embodiment and comparative example are shown in Table 4.

[0068] Table 4 Electrical and Barrier Properties Results Analysis As can be seen from the data in Tables 1 to 4, the schemes in Examples 1 to 5 all achieved excellent comprehensive performance, especially Example 1, which had a gel content of 52%, a Vicat softening temperature of 131℃, longitudinal and transverse heat shrinkage rates of only 0.32% and 0.28% at 150℃, a longitudinal tensile strength of 48.6 MPa, a plasticizer weight loss of only 0.8% after 28 days, a 76% elongation at break retention rate after aging at 85℃ / 85%RH for 3000 hours, and a volume resistivity of 6.2 × 10¹. 4 Ω·cm, all performance characteristics are significantly better than the conventional requirements for photovoltaic backsheets. Example 2 uses a lower CPVC ratio, the Vicat softening temperature and tensile strength are slightly lower but still remain at a high level, the elongation at break is improved, and it shows better flexibility; Example 3 uses a higher CPVC ratio, the heat resistance and rigidity are further improved, but the elongation at break is slightly lower; Example 4 uses a lower amount of plasticizer, the film rigidity and heat resistance are improved; Example 5 uses a higher amount of plasticizer, the flexibility is improved but the heat resistance and plasticizer retention rate are slightly lower.

[0069] Comparative Example 1 is a traditional flexible PVC film formulation with a Vicat softening temperature of only 65°C, a heat shrinkage rate of up to about 5% at 150°C, a plasticizer weight loss of 12.6% after 28 days, a performance retention rate of less than 30% after damp heat aging, and a volume resistivity on the order of 10¹²Ω·cm. All of its performance is far lower than that of the example and cannot meet the requirement of a 25-year service life for photovoltaic backsheets.

[0070] The only difference between Comparative Example 2 and Example 1 is the absence of a silane crosslinking system. Data comparison shows that Comparative Example 2 has a gel content of 0, a Vicat softening temperature of 97°C, which is 34°C lower than Example 1; a heat shrinkage rate of 2.4% at 150°C, which is 7.5 times that of Example 1; a plasticizer weight loss of 5.4% after 28 days, which is 6.8 times that of Example 1; and an elongation retention rate of only 58% after aging at 85°C / 85%RH for 3000 hours, which is 18 percentage points lower than that of Example 1. This indicates that the Si-O-Si three-dimensional network structure formed by the silane crosslinking system not only significantly improves the heat resistance and dimensional stability of the film, but also inhibits plasticizer migration through a physical sieving effect, thereby improving the film's durability in humid and hot environments. Without crosslinking, the CPVC / PVC alloy alone cannot control the heat shrinkage rate below 1.5%.

[0071] The difference between Comparative Example 3 and Example 1 is that chopped glass fibers were not added. The longitudinal heat shrinkage rate of Comparative Example 3 at 150°C was 1.05%, which, although a significant improvement compared to Comparative Example 2, was still higher than the 0.32% of Example 1; the tensile strength was 40.7 MPa, approximately 8 MPa lower than Example 1; however, the right-angle tear strength was 163 N / mm, higher than the 132 N / mm of Example 1. This indicates that, based on the silane crosslinking network and nanofillers, glass fibers provide micron-level skeletal support, further suppressing shrinkage at high temperatures and improving tensile strength, but reducing tear strength to some extent. With the combined effect of the crosslinking system and nano-reinforcement, even without glass fibers, the heat shrinkage rate can reach 1.05%, meeting the requirement of ≤1.5%.

[0072] The difference between Comparative Example 4 and Example 1 is that the small molecule plasticizer DOP was used instead of the TOTM / polyester / ESO / EFAME composite plasticizer system of the present invention. The 28-day plasticizer weight loss of Comparative Example 4 was as high as 7.8%, nearly 10 times that of Example 1; after aging at 85°C / 85%RH for 3000 hours, the elongation retention was only 38%, while that of Example 1 was 76%; the volume resistivity after aging decreased from 10¹⁰. 4 The Ω·cm level decreased to the order of 10¹² Ω·cm; the Vicat softening temperature also decreased by 21°C. This indicates that even under the same silane crosslinking network, small molecule DOP can still easily migrate and volatilize through the network pores, leading to long-term performance degradation. However, the high molecular weight polyester plasticizer, TOTM, and epoxy plasticizer that can participate in the crosslinking reaction used in this invention achieve excellent anti-migration properties through the combination of macromolecular non-migration, covalent bonding of reactive plasticizers, and physical constraint of the crosslinking network.

[0073] The difference between Comparative Example 5 and Example 1 is that the nano-silica was not activated by silane surface grafting. The tensile strength of Comparative Example 5 was 40.2 MPa, approximately 8.4 MPa lower than that of Example 1; the elongation at break was 72%, 20 percentage points lower than that of Example 1; the gel content was 41%, lower than the 52% of Example 1; and the heat shrinkage at 150°C was also slightly higher than that of Example 1. This indicates that the surface of the silane-activated nano-silica possesses reactive double bonds and silanol groups, enabling it to participate in the grafting reaction during the twin-screw extrusion stage and in the formation of the Si-O-Si network during the post-crosslinking stage. This transforms the nano-silica from a simple physical filler into a giant crosslinking point in the crosslinking network, achieving more effective stress transfer and reinforcement through covalent bonds. Unactivated silica only has a weak physical interfacial bond with the polymer matrix, resulting in a significantly reduced reinforcement effect.

[0074] The difference between Comparative Example 6 and Example 1 is that the inorganic UV-shielding components such as rutile titanium dioxide and nano zinc oxide were removed, relying solely on doubled amounts of organic UV absorbers and hindered amine light stabilizers. Comparative Example 6 achieved a yellowing index ΔYI of 8.7 after UV aging at 60 kWh / m², more than four times that of Example 1; its tensile strength retention rate after UV aging was 72%, 17 percentage points lower than Example 1; however, other basic properties were comparable to Example 1. This indicates that the inorganic UV shielding agent blocks most UV rays at the film surface through physical reflection and absorption, significantly reducing the UV intensity reaching the organic light stabilizer layer, thereby significantly extending the effective lifespan of the organic additives. Even with doubled amounts, organic additives alone cannot continuously resist UV degradation in the long term; the organic molecules themselves are gradually consumed under UV radiation, while inorganic shielding agents do not have this consumption problem.

[0075] In summary, this invention achieves a comprehensive improvement in the film's heat resistance, dimensional stability, long-term durability, electrical insulation, and mechanical properties through the synergistic combination of a CPVC / PVC alloy matrix, a silane-grafted moisture crosslinking system, multi-scale nano- and fiber reinforcement, a combination of reactive and migration-resistant plasticizers, and an inorganic-organic triple light-stabilizing system. The film of this invention can simultaneously meet the stringent requirements of photovoltaic backsheets for laminated heat resistance, long-term outdoor durability, high insulation, and flame retardancy, while its cost is significantly lower than that of fluorinated films such as PVDF.

[0076] The above embodiments are exemplary and are intended to illustrate the technical concept and features of the present invention, so that those skilled in the art can understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made according to the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A photovoltaic backsheet film material, characterized in that, Based on parts by weight, it includes the following components: Base resin: 50-80 parts of chlorinated polyvinyl chloride, 20-50 parts of polyvinyl chloride; Plasticizer system: 20-35 parts; Heat stabilizer system: 4-6 parts; Impact modifier: 6-10 parts; Fillers and reinforcing materials: 4-6 parts of rutile titanium dioxide, 6-10 parts of nano calcium carbonate, 6-10 parts of chopped glass fiber, 1-3 parts of nano silica, and 1-2 parts of nano zinc oxide; Light-stabilized system: 0.6~1.2 parts; Crosslinking system: 1.5~2.5 parts silane coupling agent, 0.06~0.12 parts peroxide initiator, and 0.06~0.10 parts condensation catalyst.

2. The photovoltaic backsheet film material according to claim 1, characterized in that, The mass ratio of chlorinated polyvinyl chloride to polyvinyl chloride is (60~70):(30~40); The chlorinated polyvinyl chloride has a chlorine content of 63% to 69% and a degree of polymerization of 900 to 1100; the polyvinyl chloride is an SG-3 to SG-5 type suspension loose resin with a degree of polymerization of 1000 to 1500. The plasticizer system includes polyester-type plasticizers with a molecular weight of not less than 2000 and reactive plasticizers with epoxy groups; In the filler and reinforcing materials, the nano-silica is fumed silica that has been surface-grafted and activated by a vinyl silane coupling agent, and the chopped glass fibers are surface-treated with a silane coupling agent.

3. The photovoltaic backsheet film material according to claim 1, characterized in that, The plasticizer system is selected from one or more of the following: trioctyl trimellitate, dioctyl terephthalate, adipic acid polyester plasticizer, epoxidized soybean oil, and epoxidized fatty acid methyl ester; wherein, the amount of polyester plasticizer with a molecular weight of not less than 2000 is 4 to 8 parts by mass, and the total amount of reactive plasticizer with epoxy groups is 5 to 9 parts by mass, wherein the reactive plasticizer with epoxy groups is epoxidized soybean oil and / or epoxidized fatty acid methyl ester.

4. The photovoltaic backsheet film material according to claim 1, characterized in that, The heat stabilizer system is selected from one or more of calcium-zinc composite stabilizers, β-diketone stabilizers, phosphite auxiliary stabilizers, and magnesium-aluminum hydrotalcite; the impact modifier is selected from one or two of acrylate core-shell structure impact modifiers, chlorinated polyethylene, and methyl methacrylate-butadiene-styrene copolymer.

5. The photovoltaic backsheet film material according to claim 1, characterized in that, The rutile titanium dioxide has an average particle size of 0.2~0.3μm; the nano-calcium carbonate has an average particle size of 40~80nm; the chopped glass fiber has a fiber diameter of 10~15μm and a length of 2~4mm; the nano-silica is fumed silica with a specific surface area of ​​150~250m² / g and a primary particle size of 10~25nm; and the nano-zinc oxide has an average particle size of 30~50nm.

6. The photovoltaic backsheet film material according to claim 1, characterized in that, The light-stabilizing system is selected from one or more of benzotriazole ultraviolet absorbers, hindered amine light stabilizers, and hindered phenolic primary antioxidants; the silane coupling agent is vinyltrimethoxysilane or vinyltriethoxysilane; the peroxide initiator is dicumyl peroxide or benzoyl peroxide; and the condensation catalyst is dibutyltin dilaurate or dibutyltin diacetate.

7. A method for preparing a photovoltaic backsheet film material as described in any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Dry chlorinated polyvinyl chloride resin and polyvinyl chloride resin until the moisture content drops to below 0.3%; pre-treat nano-silica with a vinyl silane coupling agent for surface grafting activation; dry nano-calcium carbonate; (2) After drying, chlorinated polyvinyl chloride, polyvinyl chloride, heat stabilizer, impact modifier, rutile titanium dioxide, nano calcium carbonate, activated nano silica, nano zinc oxide, and light stabilizer are premixed and added to the main feed port of a co-rotating twin-screw extruder; liquid plasticizer is metered and injected from the middle section of the extruder; chopped glass fiber is added from the side feed port of the rear section of the extruder; silane coupling agent and peroxide initiator dissolved therein are injected from a special metering pump in the rear section of the extruder; extrusion granulation is performed to obtain silane grafted alloy granules; (3) The condensation catalyst is melt-mixed with polyethylene wax, cooled and solidified, then crushed and sieved to prepare catalyst master powder; the silane grafted alloy granules are mixed with the catalyst master powder, and discharged after cold mixing; (4) After the cold-mixed material is plasticized by internal mixing or open milling, it is sheeted and then calendered into film by calendering machine; (5) After calendering, the film is cooled, trimmed, and wound up; (6) The wound film is placed under constant temperature and humidity conditions for post-crosslinking treatment, and then cooled and dried to obtain the finished film.

8. The preparation method according to claim 7, characterized in that, The temperatures of each section of the co-rotating twin-screw extruder in step (2) are as follows: Zone 1 130~140℃, Zone 2 145~155℃, Zone 3 155~165℃, Zone 4 160~170℃, Zone 5 165~175℃, Zone 6 170~175℃, Zone 7 168~172℃, Zone 8 165~170℃, Zone 9 162~168℃, and Die head 168~172℃; the screw speed is 80~120rpm, and the material residence time in the barrel is 90~150 seconds; the liquid plasticizer is metered and injected from Zone 3, the chopped glass fiber is added from the side feed port of Zone 5, and the silane coupling agent and peroxide initiator are injected from the dedicated metering pump in Zone 6; Zone 8 is equipped with vacuum exhaust, and the vacuum degree is -0.08~-0.095MPa.

9. The preparation method according to claim 7, characterized in that, The calender mentioned in step (4) is a five-roll calender, and the temperatures of each roll are: 165~170℃ for roll #1, 170~175℃ for roll #2, 175~180℃ for roll #3, 172~177℃ for roll #4, and 168~173℃ for roll #5; the final roll gap is 1.08~1.12 times the target film thickness; and the calendering line speed is 8~12m / min.

10. The preparation method according to claim 8, characterized in that, In step (5), the film roll is cooled by 5 to 7 cooling rollers in a stepwise manner, with the temperature of the cooling rollers decreasing from 105 to 115°C to 20 to 30°C in turn; the winding tension is 3 to 5 N / cm, and the film roll is kept in a loose winding state. The conditions for the post-crosslinking treatment in step (6) are: temperature 75~85℃, relative humidity 90%~98%, treatment time 20~28 hours; cooling rate not exceeding 1.5℃ / min.